Accurate quantification of total bacteria in raw milk by flow cytometry using membrane potential as a key viability parameter. (1st January 2023) - Wang, Meng; Bai, Zhaoying; Liu, Siyuan; Liu, Yingying; Wang, Ziquan; Zhou, Guoping; Gong, Xiaoyun; Jiang, You; Sui, Zhiwei
Abstract: Total bacterial count (TBC) is one of the most widely accepted indicators to evaluate raw milk quality. Rapidly quantifying TBC, by flow cytometry (FCM) coupled with viability indicators, is increasingly being preferred over time-consuming cultivation-based methods. However, whether viability indicators accurately identify viable bacteria, challenged by natural stresses, remains largely unexplored. Here, three typical milk-borne species were challenged with representative dairy farm disinfection conditions to identify the optimal viability parameter through multiparameter FCM, which has not been attempted so far. We demonstrated that only the membrane potential accurately distinguished between viable and dead cells under stress and exhibited considerable correlation with the plate counting method, despite that all viability parameters recognized highly active and dead cells. The membrane potential indicator, DiBAC4(3), was first combined with SYTO64 to establish a novel FCM-based method, while formulating a conversion equation for the FCM-plate counting results. Moreover, the performance of the developed method was verified using real samples, where TBC in raw milk was accurately quantified within 2 h. Together, our results demonstrated that membrane potential optimally reflected the bacterial viability in raw milk under stress and emphasized that the viability of stressed cells should be carefully identified to quantify viable bacteria through FCM. Graphical abstract: Image 1 Highlights: A novel method was built for accurate quantify viable bacterial cells in raw milk. Membrane potential optimally reflects milk-borne bacterial viability under stress. DiBAC4(3) and SYTO64 were first combined to identify viable bacterial cells. A math model between flow cytometry results and plate count results was first built. The method was rapidly applied to quantify viable bacterial cells in real samples.